Working with Words A Guide to Teaching and Learning Vocabulary - Ruth Gairns; Stuart Redman (USA Cambridge University Press, 1986)
This is a practical guide for teachers on how to select, organise and teach vocabulary to all levels of students. It discusses the linguistic and psychological theories relevant to vocabulary learning, describes with clear examples traditional and current methods of presentation and practice, and suggests ways of assessing and supplementing the vocabulary component of coursebooks. Working with Words is an ideal resource for practising teachers and teachers in training.